High intensity x-ray interaction with a model bio-molecule system: double-core-hole states and fragmentation of formamide. (20th November 2020) - Koulentianos, D; Fouda, A E A; Southworth, S H; Bozek, J D; Küpper, J; Santra, R; Kryzhevoi, N V; Cederbaum, L S; Bostedt, C; Messerschmidt, M; Berrah, N; Fang, L; et al.
Abstract: Formamide, a simple model bio-molecule (HCONH2 ), is irradiated with high intensity, ultrashort pulses from an x-ray free electron laser. Ionic fragments resulting from photoionization and subsequent decay processes are recorded, as well as the electronic signature of the different inner shell ionization events that can take place during the x-ray pulses. The formation of double-core-hole states, where a second inner shell electron is removed before the first core hole has been refilled is observed in the electron spectra, recorded at all three sites (C, N, O) of the molecule. The individual ionization potentials are compared with results of ab initio calculations at different level of theory. Based on our results, future opportunities for advanced studies of inner-shell-induced electronic and nuclear dynamics are explored.